The Significance of Social Capital in the Higher Agricultural Education System - Shiri, Nematollah; Naderi, Nader (International Journal of Agricultural Management and Development, 2015)
The academic achievement of students has been a focus of social research for decades. Yet little attention has been paid to social capital and its importance as a university context factor for academic success. We examine whether social capital has effects on students’ academic achievement. The population of this study consisted of all senior agricultural students of Razi University at Iran (N=257), that 154 of them were selected as the sample using the proportionate stratified sampling method. The main instrument in this study was a questionnaire which its validity was confirmed by a panel of experts and its reliability was established by Cronbach’s Alpha coefficient (α>0.70). Data was analyzed by SPSS Win22 and LISREL 8.80 software in two phases of descriptive and inferential statistics. Results of structural equation modeling indicated that social capital was the main predictor of agricultural students’ academic achievement. Findings of this study can have practical implications concerning agricultural students’ academic achievement for higher agricultural education mangers, planners and educators.